The influence of business experience and accounting knowledge on business success through MSME management - Ronaldy Iyaku; Darman; Dedy Suryadi (KIRANA : Social Science Journal, 2026)
This explanatory quantitative study aims to examine and analyze the impact of entrepreneurial experience and accounting knowledge on business success, mediated by MSME management. The study population consists of all MSME operators in Gorontalo City, with a sample selected using the purposive sampling method. Data were collected via questionnaires (both in-person and online) and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS. Data processing stages included descriptive statistics and outer model testing (specifically convergent validity via loading factors and Average Variance Extracted/AVE). Initial testing revealed that indicators PP1, PP3, and KU2 had loading factors below 0.70. Nevertheless, the instrument remained valid as the AVE values for all variables exceeded 0.50. Following adjustments—specifically the removal of those non-significant indicators—all remaining indicators achieved loading factors above 0.70. The resulting AVE values were: Business Experience (0.676), Accounting Knowledge (0.599), Business Success (0.709), and MSME Management (0.750). These results demonstrate that the research instrument met ideal convergent validity standards; thus, the data were deemed valid and ready for the subsequent structural model (inner model) analysis.